2018
DOI: 10.1002/pon.4943
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between body image and health‐related quality of life in Chinese cancer survivors during the transitional cancer survivorship

Abstract: Background: Previous research has documented the negative impact of cancer treatment on body image and health-related quality of life among survivors, and the positive relationship between those factors. However, existing evidence is mainly based on Western studies of female survivors, and there is thus a huge knowledge gap in research on non-Western cancer survivors. Objectives: The aim of the study was to assess body image and health-related quality of life, and explore their relationship, among Chinese canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Research in the literature has indicated that individuals diagnosed with cancer often experience a reduced quality of life [23]. Improving the quality of life in patients diagnosed with breast cancer should be one of the important objectives [24].…”
Section: Discussionmentioning
confidence: 99%
“…Research in the literature has indicated that individuals diagnosed with cancer often experience a reduced quality of life [23]. Improving the quality of life in patients diagnosed with breast cancer should be one of the important objectives [24].…”
Section: Discussionmentioning
confidence: 99%